PENGARUH KOMUNIKASI INTERPERSONAL KEPALA BIDANG TERHADAP TINGKAT STRES KERJA PEGAWAI - Alma Intan Fadilla (Universitas Pendidikan Indonesia, 2021)
Background research on the problem of how much influence the head of the field interpersonal communication has on the level of work stress of employees in the field of Senior High School Development at the Education Office of West Java Province. The research method used is a descriptive method supported by literature study. The technique carried out in this study consists of two stages. In the early stages, questionnaires were distributed via Google Form to the West Java Provincial Education Office in the PSMA Sector, the second was to test the validity and reliability tests, and data analysis while the total population of this study was 37 people, and the number of samples was the same as the population because it used the technique. total sampling. Based on the results of data processing calculated using the Weight Means Scores (WMS) technique, it shows that the general trend for variable X (Interpersonal Communication) is 4.33 and is in the very good category. Meanwhile, the average general trend for variable Y (Job Stress) is 4.22 which is in the very good category. The results of the calculation of the normality test of the distribution show that the X and Y variables are normally distributed. Judging from the calculation of the correlation coefficient (Tcount) using the Perason Product Moment formula, the correlation coefficient value is 0.402. This shows that there is a strong enough relationship between the Y variable. The results of the significant test with the t-test show that the t-test is 2,595 and it is known that the t-table is 1.689 when compared, then tcount ttable. To determine the influence of variable X and variable Y is shown from the calculation of the analysis of the coefficient of determination (KD) of 16.1%. Based on the results of the above research, it can be concluded that the research hypothesis is that there is a positive and significant influence between the Head of Field Interpersonal Communication on the Work Stress Level of Employees in the Field of Senior High School Development at the Education Office of West Java Province. The results of this study are expected to provide a benefit both for institutions, employees and for future researchers who will examine communication problems on the level of work stress.